Writing and the West German Protest Movements The Textual Revolution - Puw Davies, Mererid (imlr books, 2020)
The 1960s protest movements marked an astonishing moment for West Germany. They developed a political critique, but are above all distinctive for their overwhelming emphasis on culture and the symbolic. In particular, reading and writing had a uniquely prestigious status for West German protesters, who produced an extraordinary textual culture ranging from graffiti and flyers to agit-prop poetry and autobiographical prose. By turns witty, provocative, reflective and offensive, the avantgarde roots of anti-authoritarianism are as palpable in their texts as their debt to high literature. But due to this culture's (apparently) anti-literary tone, it has often remained illegible to traditional criticism. This volume presents close readings and analyses of emblematic examples of texts, some forgotten, others better known, embedding them in historical, cultural, theoretical and aesthetic context, and illuminating representative moments and preoccupations in anti-authoritarian culture, from the Vietnam War to the Nazi past, to dirt and hygiene. They outline an anti-authoritarian poetics and uncover some of the texts' latent content, revealing often hidden tensions and contradictions, above all in relation to the German past and questions of authority.